PENGONTROL MOTOR KONVEYOR (BAN BERJALAN) - Maslihan (Universitas Mitra Karya, 2019)
Conveyors are the main mover in industrial processes, automation in conveyor operations is needed to increase company efficiency and productivity. In this thesis, a conveyor drive motor control system is designed based on the rotation parameters of the shredder motor as a reduced form of the actual size, as a model to understand the working principle and control of the conveyor drive motor using a motor scale in the laboratory. Fruit conveyor systems in industries are used to bring (herd) fruit into the aisle of the fruit crushing chamber. Control is carried out by varying the voltage at the input of the thyristor control circuit, which is carried out by changing the ignition angle (triggering) of the thyristor according to the assumption that the motor is driven in the Agrokusuma home industry as a comparison to the original scale with the laboratory scale. The motor functions as a driver by using a thyristor component as a speed regulator and using the LM3915 IC component to regulate the trip voltage level sensor. The test results show that the design of an automatic fruit shredder feeding control system can function according to predetermined specifications, which means that the speed of the shredder motor is linear with the conveyor motor so that there is a balance of fruit supply to the shredder motor by the conveyor motor. ABSTRAK Konveyor merupakan penggerak utama dalam proses industri, otomatisasi dalam pengoperasian konveyor sangatlah diperlukan untuk peningkatan efisiensi dan produktivitas perusahaan. Dalam skripsi ini dirancang sistem pengaturan motor penggerak konveyor berdasarkan perameter putaran motor shredder sebagai bentuk tereduksi dari ukuran sesungguhnya, sebagai model untuk memahami prinsip kerja dan pengendalian motor penggerak konveyor digunakan skala motor yang ada di laboratorium. Sistem konveyor buah di industri-industri digunakan untuk membawa (menggiring) buah untuk masuk ke dalam lorong ruang penghancur buah. Pengendalian dilakukan dengan memberikan variasi tegangan pada masukan rangkaian pengendali thyristor, yang dilakukan dengan mengubah-ubah sudut penyalaan (pemicuan) thyristor yang sesuai untuk pengasumsian penggerak motor yang berada di agrokusuma home industry sebagai pembanding skala asli dengan skala laboraturium. Motor berfungsi sebagai penggerak dengan menggunakan komponen thyristor sebagai pengatur kecepatan dan menggunakan komponen IC LM3915 untuk pengatur sensor level trip tegangan . Hasil pengujian menunjukkan bahwa rancangan sistem pengendalian otomatis fruit shredder feeding dapat berfungsi sesuai dengan spesifikasi yang telah ditetapkan yang artinya kecepatan motor shredder bersifat linier dengan motor konveyor sehingga terjadi keseimbangan suplai buah pada motor shredder oleh motor konveyor